Myriocin Effect on Tvrm4 Retina, an Autosomal Dominant Pattern of Retinitis Pigmentosa - Piano, Ilaria; D’Antongiovanni, Vanessa; Novelli, Elena; Biagioni, Martina; Dei Cas, Michele; Paroni, Rita Clara; Ghidoni, Riccardo; Strettoi, Enrica; Gargini, Claudia (Frontiers in Neuroscience, 2020)
Tvrm4 mice, a model of autosomal dominant Retinitis Pigmentosa (RP), carry a mutation of Rhodopsin gene that can be activated by brief exposure to very intense light. Here we test the possibility of an anatomical, metabolic and functional recovery by delivering to degenerating Tvrm4 animals, Myriocin, an inhibitor of ceramide de novo synthesis previously shown to effectively slow down retinal degeneration in rd10 mutants (Strettoi et al., 2010; Piano et al., 2013). Different routes and durations of Myriocin administration were attempted by using either single intravitreal (i.v.) or long-term, repeated intraperitoneal injections (i.p.). The retinal function of treated and control animals was tested by ERG recordings. Retinas from ERG recorded animals were studied histologically to reveal the extent of photoreceptor death. A correlation was observed between Myriocin administration, lowering of retinal ceramides and preservation of ERG responses in i.v. injected cases. Noticeably, the i.p. treatment with Myriocin decreased the extension of the retinal-degenerating area, preserved the ERG response and correlated with decreased levels of biochemical indicators of retinal oxidative damage. The results obtained in this study confirm the efficacy of Myriocin in slowing down retinal degeneration in genetic models of RP independently of the underlying mutation responsible for the disease, likely targeting ceramide-dependent, downstream pathways. Alleviation of retinal oxidative stress upon Myriocin treatment suggests that this molecule, or yet unidentified metabolites, act on cellular detoxification systems supporting cell survival. Altogether the pharmacological approach chosen here meets the necessary pre-requisites for translation into human therapy to slow down RP.